The ‘Business’ of hair: the meaning of hair for Southern African Black women - Matjila, Cheri R. (University of the Free State, 2020)
Hair carries different meanings all over the world and reflects our interconnected globe, as well as our regional and local histories. For many years, black people in Southern Africa have had to assimilate to dominant Eurocentric beauty standards with respect to hair. This, particularly for black women, was and continues to be a locus of social, physical and emotional oppression. Major events in history such as the Transatlantic Slave Trade, racial segregation, and apartheid have played an important role in influencing the complex relationship that black women have with their hair, in and beyond the region. As a result of this turbulent history, the Natural Hair Movement strives to fight against stereotypes about black women’s hair, including the related issues of racism and discrimination. However, the paths towards embracing natural hair are diverse and encapsulate a complexity which escapes singular and simplistic interpretations. This study explores the nuanced and diverse meanings, and practices that surround hair for black women in contemporary Namibia and South Africa. The hair journey of black women is intricate and often escapes representations that reduce hair to debates surrounding opposing labels of ‘natural’ or ‘un-natural’. Seven women participated in this ethnographic research and shared their perspectives on hair in general, and “natural hair” in particular. These women reside in Windhoek, Namibia and in Bloemfontein, South Africa. The results revealed that the relationship that black women have with natural hair is often strongly related to processes of identity formation. In some cases, these processes were shaped by women’s efforts at daily hair maintenance and socio-economic concerns. In others, they reflected black women’s deeper spiritual and metaphysical connection with natural hair. Furthermore, it is evident from the results that affinity towards natural hair can also be an important form of social activism. Therefore, regardless of whether or not black women view their hair choices politically, wearing natural hair is a stand against Eurocentric beauty standards, thus altering the relationship that black women have with hair. In essence, this thesis illustrates the importance of hair for black women in Southern Africa and the multiplicity of meanings that are attached to it. In addition, it also stresses the need to liberate and decolonise the mindset of black communities regarding hair, and to wean young black girls from the Eurocentric subliminal messages of hair care companies.
Dissertation (M.Soc.Sc. (Anthropology))--University of the Free State, 2020
Keywords: Hair; Natural Hair Movement; Black women; Identity formation; Spirituality; Freedom; Beauty; Pain; Discrimination; Racism